Morphology of spermathecae of some pentatomids (Hemiptera: Heteroptera: Pentatomidae) from Turkey - Candan Selami̇; Yilmaz, Fatma Sümeyye; Suludere Zeki̇ye; Erbey, Mahmut (Zootaxa, 2015)
The spermathecal morphology of nine species belonging to the Pentatomidae (Insecta: Heteroptera) were compared by optical and scanning electron microscopy (SEM). Among the examined species [Rhaphigaster nebulosa (Poda 1761), Palomena prasina (Linnaeus 1761), Piezodorus lituratus (Fabricius 1794), Graphosoma lineatum (Linnaeus 1758), Graphosoma semipunctatum (Fabricius 1775), Aelia albovittata (Fieber 1868), Codophila varia (Fabricius 1787), Ancyrosoma leucogrammes (Gmelin 1790), Nezara viridula (Linnaeus 1758)], all spermathecae contained a spermathecal bulb (reservoir), a pumping region, distal and proximal flanges, proximal and distal spermathecal ducts, dilation of spermathecal duct and a genital chamber containing two ring sclerites, but each species had a different spermathecal morphology.